Benefit Segments for Full-Time Undergraduate Students - Church, John H.; Gillingham, David W. (Canadian Journal of Higher Education, 1988)
The purpose of this article is to present the results of a case analysis conducted at Laurentian University in Sudbury, Ontario. The objective of this case study was to identify the benefits sought by undergraduate students and to form meaningful groups, or segments, based upon these benefits. A sample of 427 full-time at Laurentian University was used for this investigation. A questionnaire to gather information on the student, this included 19 questions using Likert statements to measure the perceived benefits of a university education. Factor analysis was used to identify five underlying benefit dimensions which were subsequently labelled as: personal skill development; personal advancement; social pressure; learning and discovering; and intellectual development. Cluster analysis, based upon the factor scores, was used to form groups of students seeking similar benefits. Six groups, or segments, were formed and named as: self improvement; pressure; learning; self development; career; and continue to study favourite subject. These groups were found to have significantly different scores on a wide range of variables. Whilst this study was limited to the students at Laurentian University nevertheless university administrators should find this study useful as a case study of applying market segmentation to educational markets.